2020
DOI: 10.1525/mp.2020.38.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Timing Is Everything…Or Is It? Effects of Instructed Timing Style, Reference, and Pattern on Drum Kit Sound in Groove-Based Performance

Abstract: This study reports on an experiment that tested whether drummers systematically manipulated not only onset but also duration and/or intensity of strokes in order to achieve different timing styles. Twenty-two professional drummers performed two patterns (a simple “back-beat” and a complex variation) on a drum kit (hi-hat, snare, kick) in three different timing styles (laid-back, pushed, on-beat), in tandem with two timing references (metronome and instrumental backing track). As expected, onset location corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…For the same reason, we shouldn't take the studies cited above (which examine the impact of microtiming variations on audience members' desires to move to the music) as evidence against Keil, Iyer, or Roholt (except where they tie their accounts to groove-as-movement). Indeed, there is robust evidence that, despite not doing it when asked to increase or add groove, musicians do undertake the kinds of modifications and variations that musical nuance theorists describe (Camara 2016;Camara et al 2020;Polack & London 2014). However, these studies operationalize groove according to the broad definition of groove-as-feel.…”
Section: Two Concepts Of Groove |mentioning
confidence: 99%
See 1 more Smart Citation
“…For the same reason, we shouldn't take the studies cited above (which examine the impact of microtiming variations on audience members' desires to move to the music) as evidence against Keil, Iyer, or Roholt (except where they tie their accounts to groove-as-movement). Indeed, there is robust evidence that, despite not doing it when asked to increase or add groove, musicians do undertake the kinds of modifications and variations that musical nuance theorists describe (Camara 2016;Camara et al 2020;Polack & London 2014). However, these studies operationalize groove according to the broad definition of groove-as-feel.…”
Section: Two Concepts Of Groove |mentioning
confidence: 99%
“…However, these studies operationalize groove according to the broad definition of groove-as-feel. For instance, one study found reliable microrhythmic variations among drummers who were asked to perform in either a 'laid-back', 'on-the-beat', or 'pushed' style (Camara et al 2020). While the extent to which these findings vindicate any particular theory of groove-as-feel might depend on the details of whether the microtiming variations that researchers are looking at qualify as musical nuances on Raffman's account, these findings do suggest that microtiming variations (of some kind) play a very important role in generating and preserving certain musical feels (grooves on the groove-as-feel model).…”
Section: Two Concepts Of Groove |mentioning
confidence: 99%
“…-Microtiming was discussed as potentially relevant to the urge to move, but empirical results were inconsistent (Brøvig-Hanssen et al, 2021, Câmara et al, 2020a, 2020b, Cameron et al, 2019Datseris et al, 2019;Davies et al, 2013;Engel et al, 2022;Frühauf et al, 2013;Ganis et al, 2021;Hofmann et al, 2017;Keil, 1987;Kilchenmann & Senn 2015;Matsushita & Nomura, 2016;Nelias et al, 2022;Senn et al, 2016;Skaansar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…• Microtiming was discussed as potentially relevant to the urge to move, but empirical results were inconsistent (Brøvig-Hanssen et al, 2021;Câmara et al, 2020aCâmara et al, , 2020bCameron et al, 2019;Datseris et al, 2019;Davies et al, 2013;Engel et al, 2022;Frühauf et al, 2013;Ganis et al, 2021;Hofmann et al, 2017;Keil, 1987;Kilchenmann & Senn 2015;Matsushita & Nomura, 2016;Nelias et al, 2022;Senn et al, 2016;Skaansar et al, 2019).…”
mentioning
confidence: 99%
“…The properties of the music itself (Figure 1, left box, “Musical Properties”) have been investigated extensively in groove research as causes of the urge to move. The studies primarily address the following topics: Microtiming was discussed as potentially relevant to the urge to move, but empirical results were inconsistent (Brøvig-Hanssen et al, 2021; Câmara et al, 2020a, 2020b; Cameron et al, 2019; Datseris et al, 2019; Davies et al, 2013; Engel et al, 2022; Frühauf et al, 2013; Ganis et al, 2021; Hofmann et al, 2017; Keil, 1987; Kilchenmann & Senn 2015; Matsushita & Nomura, 2016; Nelias et al, 2022; Senn et al, 2016; Skaansar et al, 2019). Syncopated rhythm has been found to affect the urge to move.…”
mentioning
confidence: 99%